Fast-tracking industrialization in Tanzania the must-do-actions - Msambichaka, Lucian (Dar es Salaam Dar es Salaam University Press, 2020)
This book looks into the circumstances and challenges facing Tanzania in its endeavor to industrialise, and proposes the must do actions to achieve this objective.It attempts to show ways on how to fast-track the industrialization process and hence hasten its positive impact on Tanzania's economy and the welfare of its people.
Keywords: Industrialization